Bacterial community structure and metabolic activity of drinking water pipelines in buildings: A new perspective on dual effects of hydrodynamic stagnation and algal organic matter invasion. (15th October 2022) - Zhang, Haihan; Zhao, Kexin; Liu, Xiang; Chen, Shengnan; Huang, Tinglin; Guo, Honghong; Ma, Ben; Yang, Wanqiu; Yang, Yansong; Liu, Hanyan
Highlights: Water quality deterioration caused by AOM and hydrodynamic stagnation. Bacterial community structure was explored in drinking water combined different AOM. Network showed the co-occurrence patterns among bacterial communities. Structural equation model was built between AOM and bacteria. Abstract: Eutrophication and algal blooms have become global issues. The drinking water treatment process suffers from pollution by algal organic matter (AOM) through cell lysis during the algal blooms. Nevertheless, it remains unclear how AOM invasion affects water quality and microbial communities in drinking water, particularly in the stagnant settings. In this study, the addition of AOM caused the residual chlorine to rapidly degrade and below the limit of 0.05 mg/L, while the NO2 − -N concentration ranged from 0.11 to 3.71 mg/L. Additionally, total bacterial counts increased and subsequently decreased. The results of Biolog demonstrated that the AOM significantly improved the utilization capacity of carbon sources and changed the preference for carbon sources. Full-length 16S rRNA gene sequencing and network modeling revealed a considerable reduction in the abundance of Proteobacteria, whereas that of Bacteroidetes increased significantly under the influence of AOM. Furthermore, the species abundance distributions of the Microcystis group and Scenedesmus group was most consistent with the Mandelbrot model. According to redundancy analysis and structural equation modeling, the bacterial community structure of the control group was most positively regulated by the free residual chlorine concentrations, whereas the Microcystis group and Scenedesmus group were positively correlated with the total organic carbon (TOC) concentration. Overall, these findings provide a scientific foundation for the evolution of drinking water quality under algae bloom pollution. Graphical abstract: Image, graphical abstract